Targeted review of maximum residues levels (MRLs) for haloxyfop‐P. (18th November 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: In compliance with Article 43 of Regulation (EC) No 396/2005, the European Food Safety Authority (EFSA) received a mandate from the European Commission to perform a targeted review of the existing maximum residues levels (MRLs) for the active substance haloxyfop‐P to check whether the existing EU MRL in onions, sunflower seeds and soya beans (covering codex maximum residue limits (CXLs) or import tolerances) and the proposed import tolerance MRLs in linseeds, rapeseeds/canola seeds are safe for consumers and can eventually be maintained in the MRL Regulation after the expiry of the approval of the active substance. EFSA screened these MRLs considering the toxicological reference values established during the EU peer review process for the renewal of the approval of haloxyfop‐P and identified chronic consumer intake concerns for two diets when for the remaining plant and animal commodities, the input values were at the LOQ. Fall‐back MRLs could not be proposed, but the additional information provided by EURLs allowed to resolve the chronic intake concerns using lower validated LOQs for a range of plant commodities and milk. EFSA concludes that the existing EU MRLs in soya beans and onions, the CXL in sunflower seeds and the proposed import tolerances in linseed and rapeseed/canola seeds are not expected to pose a risk to consumers. However, to guarantee consumer's safety regarding the chronic exposure to haloxyfop‐P residues, the enforcement LOQs in several plant commodities and milks would have to be lowered to the levels reported by the EURLs.